Degradation of Shielding Performance of Metallic Sheet due to Aperture Configuration and Dimension at 2.4 GHz - Adik Susilo Wardoyo; Mudrik Alaydrus (Jurnal Elektronika dan Telekomunikasi, 2018)
The increasing demand on wireless connectivity has opened new and modern communication systems. Many wireless systems, for example Wireless Fidelity (Wi-Fi), Bluetooth, ZigBee, share the unlicensed frequency region around 2.4 GHz. Due to intensive application of Wi-Fi systems, there are certain disturbance potentials observed. The Wi-Fi signals cause interference to ZigBee networks which are used for smart grid applications. In this work, the shielding effectiveness of a metallic enclosure with several apertures is studied. Based on analytical expression from the literature, the shielding effectiveness by varying the sheet thickness, number of apertures, and aperture patterns is calculated. Several measurements of Received Signal Strength Indicator (RSSI) are carried out. The measurements are conducted on a shielded room to isolate the measurement from other unknown signal sources. The calculation and measurement of shielding effectiveness confirmed that more apertures on a shielding sheet will reduce the Shielding Effectiveness (SE). SE for one aperture for the case sheet thickness 0.7 mm and diameter of 12 mm reduce from 46.28 dB to 14.24 dB for 6 apertures. Bigger aperture diameters will also degrade the SE from 46.28 dB to 5.27 dB for aperture diameter 24 mm. The same condition can be concluded for the thickness 1.4 mm for aperture diameter of 12 mm. However a slightly different measurement results are obtained for the thickness 1.4 mm and aperture diameter of 24 mm. The thickness plays a significant role to attenuate the wave, so that SE is bigger than the calculated one.